SOS Smart Reminder and Emergency Detection Device Using ESP8266 and MPU6050 - Deepashree, H.S.; Manjula Sanjay, Koti; Yap, Choi Sen (INTI International University, 2024)
Research indicates that approximately 85% of deaths are caused by heart attacks, strokes, shortness of breath, and other medical conditions could be prevented through timely treatment. Hence, immediate access to an easily reachable SOS button plays a vital role in providing prompt assistance. Vehicle accidents result in a significant number of fatalities. Delays in reaching the hospital contribute to about 76% of deaths in each vehicle category. An urgent solution is needed: a gadget or technology capable of detecting collisions and promptly alerting their local guardians. This would enable immediate medical assistance, potentially saving lives and reducing the fatality rate associated with such accidents. The current work is driven by three key factors: the necessity for a dedicated device to remind patients with chronic illnesses to take their medications at the prescribed times, the absence of a convenient SOS button readily accessible during emergencies, and the delay in communication between accidents and contacting guardians. The authors in this study emphasizes the importance of timely medical care and interventions which significantly decrease mortality rates associated with these conditions. Not adhering to medication schedules and taking incorrect medicines at inappropriate times can have serious consequences. A specialized reminder device that prompts individuals with medication names at specific times is necessary to ensure proper administration and improve health outcomes.